An Overview of Foreign Long-Range Precise Air Striking Development - Gao Shuliang, Fan Sisi, Yuan Cheng, Cao Junwei (Hangkong bingqi, 2023)
Long-range air striking is an important trend in the modern air operations. This paper focuses on the development of equipment, technology, and operation concepts in long-range air strike domain in foreign countries, analyzes the main research status in this field and summarizes the development trends in operation concepts, weapon platforms, and kill chains. Three typical operation modes of long-range air striking, which are collaborative target detection guided long-range striking, collaborative target indication guided long-range striking and networked relayed guided long-range striking, are proposed from the perspective of how guidance information is generated. Based on the development situation in foreign countries, key technologies supporting long-range air striking are summarized and discussed.